Sports Hernia in National Hockey League Players: Does Surgery Affect Performance?. (January 2013) - Jakoi, Andre; O'Neill, Craig; Damsgaard, Christopher; Fehring, Keith; Tom, James
Background: Athletic pubalgia is a complex injury that results in loss of play in competitive athletes, especially hockey players. The number of reported sports hernias has been increasing, and the importance of their management is vital. There are no studies reporting whether athletes can return to play at preinjury levels. Purpose: The focus of this study was to evaluate the productivity of professional hockey players before an established athletic pubalgia diagnosis contrasted with the productivity after sports hernia repair. Study Design: Cohort study; Level of evidence, 3. Methods: Professional National Hockey League (NHL) players who were reported to have a sports hernia and who underwent surgery from 2001 to 2008 were identified. Statistics were gathered on the players' previous 2 full seasons and compared with the statistics 2 full seasons after surgery. Data concerning games played, goals, average time on ice, time of productivity, and assists were gathered. Players were divided into 3 groups: group A incorporated all players, group B were players with 6 or fewer seasons of play, and group C consisted of players with 7 or more seasons of play. A control group was chosen to compare player deterioration or improvement over a career; each player selected for the study had a corresponding control player with the same tenure in his career and position during the same years. Results: Forty-three hockey players were identified to have had sports hernia repairs from 2001 to 2008; ultimately, 80% would return to play 2 or more full seasons. Group A had statistically significant decreases in games played, goals scored, and assists. Versus the control group, the decreases in games played and assists were supported. Statistical analysis showed significant decreases in games played, goals scored, assists, and average time on ice the following 2 seasons in group C, which was also seen in comparison with the control group. Group B (16 players) showed only statistical significance in games played versus the control group. Conclusion: Players who undergo sports hernia surgeries return to play and often perform similar to their presurgery level. Players with over 7 full seasons return but with significant decreases in their overall performance levels. Less veteran players were able to return to play without any statistical decrease in performance and are likely the best candidates for repair once incurring injury.